Reaching out to big losers leads to sustained reductions in gambling over 1 year: a randomized controlled trial of brief motivational contact. (13th February 2020) - Jonsson, Jakob; Hodgins, David C.; Munck, Ingrid; Carlbring, Per
Abstract: Background and aims: A previous randomized controlled trial demonstrated that telephone‐ and letter‐based motivational interventions with high‐expenditure gamblers had significant short‐term positive effects on gambling and use of responsible gambling tools. This post‐trial follow‐up examined outcomes in gambling expenditure over 12 months. Design: Observational study following a three‐arm randomized controlled trial. Setting: Customers of Norsk Tipping (NT) gambling platforms, Norway. Participants: A total of 1003 statistical triplets from the top 0.5% of customers based upon annual expenditure, matched on sex, age and net losses. Mean age was 53.4 years; 19% were women, mean yearly loss for 2016 was 88 197 NoK. Interventions and comparator Feedback intervention by telephone, letter or a no‐contact control condition. Measurements: Primary outcome measure was gambling theoretical loss, derived from the NT customer database. Secondary outcomes were responsible gambling customer actions and whether or not the participant was retained as an NT customer. Findings: Per‐protocol analyses of triplets who received the telephone call or letter as randomly assigned ( n  = 596) showed a positive and sustained effect over 12 months: the telephone group showed a 30% reduction in theoretical loss ( d  = 0.44) and the letter group 13% ( d  = 0.18), both outperforming the control group with a 7% reduction ( d  = 0.11). The telephone condition was superior to both the letter and control conditions in per‐protocol ( P  < 0.001) and to control condition in intention‐to‐treat analyses (ITT) ( P  < 0.001). Individuals in the telephone condition took more responsible gambling actions. The letter condition had better outcomes than the control in the ITT‐only analysis ( P  < 0.001). More than 93% were still customers a year after the intervention. Conclusions: Personal contact with high‐expenditure gambling customers in Norway that provided individualized feedback on expenditures was associated with reduced theoretical losses and greater use of responsible gambling tools over a 12‐month period, compared with no contact. Telephone intervention with customers had a larger impact than a mailed letter.